2022-RA-681-ESGO POU2F3 driven subset of small cell carcinoma exists in the uterine cervix. (20th October 2022) - Cockenpot, Vincent; Carbonnaux, Melodie; Pissaloux, Daniel; Lantuejoul, Sylvie
Abstract : Introduction/Background: So-called tuft cell variant of small cell carcinoma is now a well-established subset of small cell carcinomas of the lung, driven by POU2F3 transcriptomic factor, and characterized by low or no expression of neuroendocrine markers. Methodology: We report here the case of a POU2F3 driven subset of small cell carcinoma of the uterine cervix, in a woman in her early 40s. This HPV-dependent carcinoma was clinically considered as primary. Immunohistochemistry and RNA-sequencing with expression and clustering analyses were performed. Results: The biopsy showed typical morphological features of small cell carcinoma. Immunohistochemistry showed no neuroendocrine markers (chromogranin A, synaptophysin) expression, but a clear POU2F3 nuclear expression, similar to that of the tuft cell variant of lung small cell carcinoma. Clustering analysis of expression data obtained by RNA-sequencing revealed an expression profile similar to that of POU2F3 driven small cell lung carcinomas. Conclusion: This variant has never been reported in uterine cervix and is worth recognizing since these tumours are usually negative for neuro-endocrine markers, and thus present a diagnostic challenge. If small cell carcinoma is first and foremost a morphological diagnosis, the use of POU2F3 imunohistochemistry as a novel diagnostic marker for these tumours with negative or low expression of neuro-endocrine markers could be helpful in clinical practice, especially on small cervix biopsy samples.